Exploring the influence of gender and tactical learning approaches on students’ enjoyment levels in physical education - Sucipto Sucipto; Burhan Hambali; Agus Gumilar; Lutfi Nur; Yusuf Hidayat (Jurnal Cakrawala Pendidikan, 2023)
Issues related to gender and learning approaches in physical education continue to be intriguing research topics. The trend of studying these variables persists year after year. However, research that combines learning approaches and gender as independent variables remains limited, particularly in studies focusing on the development of students' enjoyment in physical education. This study aims to examine the effects of the learning approach and gender on students' enjoyment. This study is an experimental study involving 56 students, comprising 28 boys and 28 girls, aged between 13 and 14 years. The students were divided into four groups. The research instrument utilized the Physical Activity Enjoyment Scale Questionnaire (PACES), designed to assess the level of student enjoyment during physical education classes. Data analysis was conducted using Two-Way ANOVA. The results of the analysis show that (1) The choice of learning approach, whether technical or tactical, significantly impacts students' enjoyment of learning, (2) Gender, whether male or female, also significantly affects student enjoyment, and (3) there is no interaction between gender and the chosen learning approach in influencing student enjoyment. In summary, both the learning approach and gender have an influence on the development of students' enjoyment, but their effects vary. Specifically, the tactical approach appears to have a more substantial impact than the technical approach. Additionally, male students exert a greater influence than female students on the development of enjoyment in physical education learning.